Gender and housing in Soviet Russia : private life in a public space - Attwood, Lynne (Gender in history, 2010)
This book explores the housing problem throughout the seventy years of Soviet history. It looks at changing political ideology on appropriate forms of housing under socialism, successive government policies on housing, and the meaning and experience of 'home' for Soviet citizens. Ultimately, it examines the use of housing to alter gender relations, and the ways in which domestic space was differentially experienced by men and women. The material, taken from Soviet magazines and journals, demonstrates how official ideas on housing and daily life changed during the course of the Soviet era, and how they were propagandised to the population. Through a series of in-depth interviews, the book also draws on the memories of people with direct experience of Soviet housing and domestic life. More than a history of housing, the book is a social history of daily life which will appeal both to scholars and those with a general interest in the Soviet era